2021
DOI: 10.3389/fendo.2021.771226
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Prognostic Factors, and Nomogram for Distant Metastasis in Breast Cancer Patients Without Lymph Node Metastasis

Abstract: BackgroundLymph node negative (N0) breast cancer can be found coexisting with distant metastasis (DM), which might consequently make clinicians underestimate the risk of relapse and insufficient treatment for this subpopulation.MethodsThe clinicopathological characteristics of N0 breast cancer patients from the Surveillance, Epidemiology, and End Results (SEER) database between January 2010 and December 2015 were retrospectively reviewed. Multivariate logistic and Cox analyses were used to identify independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…In this study, tumor size (P=0.023), low levels of albumin (P=0.024), lymphocyte to monocyte ratio (P=0.044) were independent risk factors for LNM, with age (P=0.072) and white blood cells (P=0.055) (WBCs) slightly greater than 0.05, probably due to the small sample size in this experiment. It has also been previously demonstrated that younger age and higher WBC values are strongly correlated with the spread of tumor cells (25)(26)(27)(28)(29)(30) In our study, LNM was found to be significantly correlated with tumor size (p=0.023), which is consistent with the findings of most scholars (31)(32)(33). Previous findings have also focused on the correlation between LMN and tumor size, and although lymph node metastasis was also present in tumors smaller than 1 cm.In general,it appears that larger tumor volumes are more prone to LNM.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, tumor size (P=0.023), low levels of albumin (P=0.024), lymphocyte to monocyte ratio (P=0.044) were independent risk factors for LNM, with age (P=0.072) and white blood cells (P=0.055) (WBCs) slightly greater than 0.05, probably due to the small sample size in this experiment. It has also been previously demonstrated that younger age and higher WBC values are strongly correlated with the spread of tumor cells (25)(26)(27)(28)(29)(30) In our study, LNM was found to be significantly correlated with tumor size (p=0.023), which is consistent with the findings of most scholars (31)(32)(33). Previous findings have also focused on the correlation between LMN and tumor size, and although lymph node metastasis was also present in tumors smaller than 1 cm.In general,it appears that larger tumor volumes are more prone to LNM.…”
Section: Discussionsupporting
confidence: 91%
“…Although most patients had distant metastasis 15,16 , nutritional risk 17 , no association was found between these and functionality, even though they are widely recognized as prognostic factors in cancer. Thus, it is hypothesized that these factors are not associated in the context of the last days of life.…”
Section: Discussionmentioning
confidence: 99%
“…About one-third of patients with early breast cancer will develop distant metastases (Lobbezoo et al, 2015). Numerous studies have been conducted to explore the determining factors affecting cancer metastasis (Min et al, 2021). Emerging evidence has found the impact of sleep pattern, duration, and quality on cancer metastasis.…”
Section: Dear Editormentioning
confidence: 99%